Assessing ecosystem service value dynamics and compensation gaps in key ecological zones of Xizang: towards sustainable plateau development - Du, Qianqian; Li, Lei (Frontiers in Environmental Science, 2025)
IntroductionAmid accelerating global urbanization and climate change, ecologically fragile regions such as the Xizang Autonomous Region face increasing pressure to balance ecological conservation with socio-economic development. Xizang serves as a critical ecological security barrier in China and Asia, making it an ideal case for assessing ecosystem service value (ESV) dynamics and ecological compensation needs.MethodsThis study assessed land use changes and ESV dynamics across eight key ecological function zones in Xizang from 2000 to 2020 using the value equivalent factor method, high-resolution remote sensing data, and field validation. We further proposed an ecological compensation priority score (ECPS) based on the ratio of non-market ESV to GDP per unit area.ResultsThe findings reveal a “U-shaped” trend in grassland coverage, rapid ESV gains in wetlands, and losses in snow and barren lands. Despite their limited area, water bodies contributed disproportionately to total ESV due to their strong regulatory functions. The northwestern Qiangtang Plateau desert ecological zone exhibited the highest ecological compensation priority, with a theoretical compensation amount of approximately 1.6 trillion CNY in 2020.DiscussionThe results highlight significant gaps between ecosystem service provision and current fiscal transfers. This study provides a scientific basis for improving ecological compensation mechanisms and promoting sustainable development in high-altitude ecological zones with limited economic capacity.